2006
DOI: 10.1016/j.lfs.2006.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of U83836E on nerve functions, hyperalgesia and oxidative stress in experimental diabetic neuropathy

Abstract: Oxidative stress has been implicated to play an important role in the pathogenesis of diabetic neuropathy, which is the most common complication of diabetes mellitus affecting more than 50% of diabetic patients. In the present study, we have investigated the effect of U83836E], a potent free radical scavenger in streptozotocin (STZ)-induced diabetic neuropathy in rats. STZ-induced diabetic rats showed significant deficit in motor nerve conduction velocity (MNCV), nerve blood flow (NBF) and thermal hyperalgesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…U83836E treatment significantly reduced vitreoretinal MDA levels and increased SOD activity in diabetic rats. U83836E has already been reported (a) to increase SOD levels and decrease MDA levels in mice treated with low doses of STZ [24] , (b) to ameliorate the alterations in motor nerve conduction velocity, nerve blood flow and hyperalgesia, and (c) to decrease MDA levels and increase the activities of antioxidant enzymes such as catalase and SOD in diabetic rats [14] . In addition, lipoic acid, an antioxidant, has also been reported to improve the levels of these antioxidant enzymes and to restore deficits in DR [25] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…U83836E treatment significantly reduced vitreoretinal MDA levels and increased SOD activity in diabetic rats. U83836E has already been reported (a) to increase SOD levels and decrease MDA levels in mice treated with low doses of STZ [24] , (b) to ameliorate the alterations in motor nerve conduction velocity, nerve blood flow and hyperalgesia, and (c) to decrease MDA levels and increase the activities of antioxidant enzymes such as catalase and SOD in diabetic rats [14] . In addition, lipoic acid, an antioxidant, has also been reported to improve the levels of these antioxidant enzymes and to restore deficits in DR [25] .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, a previous study showed that U83836E significantly ameliorated the alterations in motor nerve conduction velocity, nerve blood flow, hyperalgesia, malondialdehyde (MDA) levels and antioxidant enzyme levels in diabetic rats, suggesting the potential of U83836E in the treatment of diabetic neuropathy [14] . However, whether U83836E can improve neurodegeneration in DR remains uncertain.…”
Section: Introductionmentioning
confidence: 96%
“…77 There is also growing evidence that increased oxidant stress in both primary and secondary sensory neurons is a key mediator of inflammatory as well as diabetic hyperalgesia. [78][79][80][81][82][83] Whether NAPDH oxidase is the primary source of this stress has not yet been established, but it is reasonable to suspect that it is. Indeed, nerve growth factor -known to be a mediator of inflammatory hyperalgesia -promotes thermal hyperalgesia in small diameter sensory neurons by boosting the expression and axonal transport of TRPV1 (the heat receptor responsive to capsaicin); this effect has been shown to be contingent on sequential activation of Rac1, NADPH oxidase, and p38 MAP kinase.…”
Section: Nadph Oxidase In Neurons Is Potentially Pathogenicmentioning
confidence: 99%
“…In summary, hyperglycemia induces spontaneous oxidation of glucose through a variety of enzymatic and non-enzymatic activities, and increases the advanced glycation end products (AGEs), protein kinase C pathway activity, polyol pathway activity (aldose reductase), poly ADP-ribose polymerase (PARP) pathway activity, hexosamine flow, and decreases growth factors, all of which are the key components of the mentioned complex cascade. This pathway finally leads to oxidative stress of nerve cells through stimulating the production of active oxygen and active nitrogen species (30,31). Oxidative stress will eventually cause a lot of neuropathic lesions by activation of many degenerative pathways such as reduction of intracellular antioxidant enzymes activity, vascular damage, increased synthesis of free radicals in the mitochondria, decreased nitric oxide, induced endoneurial hypoxia, apoptosis, degradation of cellular components and increased expression of inflammatory factors (32).…”
Section: Discussionmentioning
confidence: 99%